VALIDITY OF SCIENCE PROCESS SKILLS TEST INSTRUMENT FOR PROSPECTIVE MI/SD TEACHER STUDENTS IN SCIENCE LEARNING - Syafrilianto, Syafrilianto; Afriandi, Muhammad; Festiyed, Festiyed; Yerimadesi, Yerimadesi; Ahda, Yuni; Alberida, Heffi (FORUM PAEDAGOGIK, 2025)
Validity refers to the degree or level of accuracy of a research instrument used to measure a variable and serves as an essential component in the development of instruments. This study aims to determine the construct and content validity of the science process skills (SPS) test instrument for the Science Learning course in the MI/SD Teacher Education Program at the State Islamic University of Sheikh Ali Hasan Ahmad Addary, Padangsidimpuan. The research method employed is a descriptive quantitative-qualitative approach, with data collected using observation sheets for the assessment of the SPS test instrument by two validators. The data from the validators' assessments were analyzed using Gregory's Test formula to determine the instrument's validity level. The results show that 13 SPS test items received validator assessments in the range of scores 3-4, categorized as highly relevant, with an overall validity score of 1 (one). Therefore, it can be concluded that the 13 test items of the science process skills instrument on the topic of temperature and heat possess a very high level of validity.